Legal History as the Perfect Vessel: Teaching with Infographics for the Development of Digital Visual Literacy Skills in Law Students - Andrea Bauling (Potchefstroom Electronic Law Journal, 2023)
Digital literacy development must be regarded equally essential as the development of other literacies and critical thinking skills in Bachelor of Laws students. Because law teachers do not include visuals in learning materials, law students do not develop the skills to effectively interpret them. Digital visual literacy (DVL) is one of the core digital literacies law teachers can advance in their students to prepare them for our visually-driven world. Legal historical course material is the perfect vessel for visual learning materials in law, as these can effectively communicate the spacio-temporal aspects of legal history and legal historical development. A recent empirical study of the views of South African students of legal history indicated their positive sentiments toward a wide variety of visual learning materials and the inclusion of instructor-generated summary infographics in online learning materials. They were also in favour of the inclusion of descriptive visuals like timeline infographics containing additional visual elements in legal historical course content. The study also indicated that reading and interpreting infographics aid the development of DVL skills, and the more infographics students interact with, the better they become at interpreting them. Since the instructor-generated summary infographic can be designed to communicate information about a specific module, it is suited to teaching any legal content. Visual learning artefacts can be created and sourced in numerous ways, but the process can be time-consuming. Sharing these amongst colleagues and institutions as open educational resources (OER) will ultimately aid a collective project aimed at the development of the DVL skills of South African law students. The article provides examples of instructor-generated summary infographics based on legal historical course content, distributed as freely available OER.